Criminal Prosperity : Drug Trafficking, Money Laundering and Financial Crisis after the Cold War. - Fabre, Guilhem (Taylor and Francis, 2013)
Drug trafficking is the most visible part of the profits of organized crime, which have grown considerably since the end of the cold war. The mirror of history shows us the impact of the drug trade in the colonization of Asia. The post cold war geopolitical context reproduces elements of the past, with new opportunities for drug trafficking in the globalization process, as can be seen in the example of China, and the lasting impunity in terms of money laundering. With the growing role of offshore locations in the global financial system, criminal prosperity has even affected the economic stabi.